2021
DOI: 10.21608/mnj.2021.213173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Cardiopulmonary Resuscitation Training Program on Nursing’ Competence

Abstract: Background: Cardiopulmonary resuscitation training is mandatory for nursing staff, whereas the ability to respond quickly and effectively to a cardiac arrest situation rests on nursing competence. Aim: to evaluate the effectiveness of structured cardiopulmonary resuscitation training program on nursing' competence. Subjects& Methods: A quasiexperimental design was used to fulfil the aim of the study. Subjects: A convenience sample of 60 critical care nurses who were recruited from critical care units. Study se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Additionally, except for the age groups of the study sample, there was no statistically significant link between any of the analyzed nurses' personal characteristics and their overall performance scores before and after a structured cardiopulmonary resuscitation training program. After completing a structured cardiopulmonary resuscitation training program, critical care nurses under study showed a clear improvement in their level of knowledge and CPR performance (Elsayed et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, except for the age groups of the study sample, there was no statistically significant link between any of the analyzed nurses' personal characteristics and their overall performance scores before and after a structured cardiopulmonary resuscitation training program. After completing a structured cardiopulmonary resuscitation training program, critical care nurses under study showed a clear improvement in their level of knowledge and CPR performance (Elsayed et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%